Sinergi Kepemimpinan Transformasional dan Budaya Organisasi: Kunci Peningkatan Motivasi Kerja Tenaga Pendidik di SMA Negeri 95 Jakarta - Lesina Samor; Nuraeni Nuraeni (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
This study addresses the issue of teachers’ work motivation, which plays a crucial role in improving educational quality but is often influenced by leadership and organizational factors. The objective of this research is to examine the effect of transformational leadership and organizational culture on teachers’ work motivation at SMA Negeri 95 Jakarta. A quantitative causal approach was employed, involving 66 teachers selected as respondents. Data were collected using structured questionnaires and analyzed through multiple linear regression using SPSS. The results indicate that transformational leadership and organizational culture have a positive and significant effect on teachers’ work motivation, both partially and simultaneously. Transformational leadership contributes through vision clarity, inspiration, and individual consideration, while organizational culture supports motivation through shared values, collaboration, and a conducive work environment. The findings highlight that the alignment between leadership style and organizational culture strengthens teachers’ motivation to perform effectively. This study implies that school management should continuously develop transformational leadership practices and reinforce a positive organizational culture to enhance teachers’ professional commitment and performance.